VD_FINDINFO 219/II vom 27. Oktober 2009 - VD Tribunal cantonal (2009)
DIVORCE SUR DEMANDE UNILATÉRALE, OPPOSITION AU DIVORCE, ABUS DE DROIT | 114 CC, 115 CC, 2 al. 2 CC, 371o al. 5 CPC, 59 let. b LDIP, 61 al. 1 LDIP